Analisis Tata Kelola Nagari Wisata berbasis CHSE dan Dampaknya terhadap Perekonomian Masyarakat Nagari - Oknaryana, Oknaryana; Kurniawati, Tri; Marwan, Marwan; Wulandari, Dwi Pratiwi (Jurnal Ecogen, 2024)
Tourism villages play an important role in tourism development. CHSE implementation will guarantee comfort and safety for tourists. This research uses a descriptive approach with surveys and FGDs to analyze the implementation of CHSE and also the economic impact of tourism on the community in Nagari Sungai Batang.The implementation of CHSE in the Nagari Sungai Batang tourist destination is starting to be seen. However, there are still various aspects of cleanliness, health, safety and environmental sustainability that can still be improved. This assessment can be an independent assessment to become a precursor to obtaining CHSE certification in the future. The existence of tourism has had an impact on the community's economy, both in terms of community income, opening up employment opportunities related to tourism and providing supporting infrastructure. However, this is also not optimal. Various efforts are still needed so that the impact of the tourism sector in Nagari Sungai Batang can give significant results. The efforts that can be carried out include tourism promotion and also determining tariffs for existing tourist destinations.